Safe and Effective Skin Antiseptics in Gastrointestinal Surgery - IIO, Megumi; SAJI, Masashi; HATA, Hiroaki (Japanese Journal of Infection Prevention and Control, 2023)
Povidone iodine, alcohol, and chlorhexidine gluconate are commonly used for skin antisepsis in surgical settings. Recently, a randomized controlled trial confirmed the effectiveness of oranexidine, a new skin antiseptic, for this purpose. However, many disinfectants are not recommended for disinfecting mucous membranes. Therefore, it is important to understand the efficacy and precautions of each agent before making a choice. This article aims to describe the indications, contraindications, and precautions for the agents frequently used in gastrointestinal surgical field antisepsis and summarize the results of recent studies on the efficacy of these agents.